Traumatic hernia of the abdominal wall. Case report - Armand Ugon Bigi, Gustavo; Ferreira Pozzi, Martín Eduardo; Arciénega Yañez, Pilar; González González, Daniel (Cirugía del Uruguay, 2021)
Male, 21 years old. Motorcycle driver, at 70 km / hour falls to the pavement, maximum impact on the right half body. ABCD-normal. Right traumatic hernia of the abdominal wall diagnosed by tomography (detachment of the broad muscles of the iliac crest, contains ileum, without elements of intestinal occlusion). Delayed laparotomic hernioplasty, polypropylene mesh placed in the preperitoneal-retromuscular plane. Very rare pathology, of clinical and / or imaging diagnosis, upon admission or delayed, traffic accidents are responsible for 78% of cases. Parietal repair, its type and timing, will be carried out depending on the patient's condition and the concomitant injuries